Tobacco use, knowledge about smoking-associated risks, and cessation programs among dental students in Germany - ToDent - Bauer-Kemény, Claudia; Lis, Ilona-Verena; Raupach, Tobias; Kreuter, Michael (Respiration, 2020)
Background: Professional and consistent smoking prevention and cessation may avoid many smoking-associated deaths worldwide. Dentists can exert a decisive influence on smoking behavior, as most people regularly visit a dentist. However, only if dentists have been trained sufficiently about the consequences of smoking and of smoking cessation methods might they fulfill this task appropriately. Objectives: The aim of our study was therefore to examine the prevalence of smokers among dental students in Germany, their attitude toward smoking in general, and their knowledge about tobacco-related diseases and smoking cessation programs. Methods: A cross-sectional survey among dental students in Germany was conducted in 2016. Students of the first and tenth semesters were asked to participate in this anonymous survey. The questionnaire included items concerning their own smoking habits, their knowledge about effects of smoking on health, and their attitude toward prevention and cessation in a dental setting. Results: Seven hundred and thirty dental students participated in this survey; 21% of the participating students were smokers. Their knowledge about smoking-related diseases was widespread. Some diseases were rarely known (only in 34% of students) and others were well known (in 99% of the students). Knowledge about health risks of e-cigarettes was low. About 30% of the participating students felt competent to encourage and support patients in cessation strategies; 2 out of 3 students were willing to improve their knowledge in that area. More than 85% confirmed that advice for smoking cessation should be one of the tasks of a dentist. Conclusions: Smoking is common among dental students, their knowledge about smoking-related health risks is moderate, and self-perceived smoking cessation skills are poor. More emphasis should be placed on education regarding smoking prevention and cessation methods.
Gesehen am 13.01.2021